The Influence of Social Media Exposure on Health Perceptions and Behaviors Among Adolescents from Broken Home Families in Indonesia: Systematic Literature Review - Murtiningsih, Nunik; Intiasari, Arih Diyaning; Wahyuningsih, Eri (Lambung Mangkurat University, 2025)
This study is a systematic literature review aimed at identifying and analyzing the influence of social media exposure on the health perceptions and behaviors of adolescents from various family backgrounds in Indonesia, including those from broken homes. The review used a quantitative-focused approach, analyzing six primary research articles published between 2015 and 2025. Findings reveal that social media significantly shapes adolescents’ understanding of physical, mental, and social health. Exposure to educational and positive content is associated with improved health awareness and behavior among the general adolescent population. In contrast, excessive engagement with toxic or unrealistic content contributes to increased stress, distorted self-perception, and unhealthy lifestyles. For adolescents from broken homes, social media serves as a psychological coping space and a source for meaning-making. However, it also carries risks if not supported by adequate digital literacy. These findings highlight the need for inclusive, empathetic, and context-sensitive digital health communication strategies and the development of supportive online communities for vulnerable youth. The review recommends future research with broader coverage and longitudinal designs to deepen the understanding of how social media influences adolescent health across different family structures.